Supercritical fluid extraction of vegetable matrices: Applications, trends and future perspectives of a convincing green technology - de Melo, M. M. R.
Along more than a decade, R&D on supercritical fluid extraction (SFE) of vegetable matrices has been increasingly reported in the literature. Aiming at portraying the current state of this field and its evolution in terms of raw materials, products, modes of operation, optimization, modeling techniques, and closeness to industrial application, a large compilation of almost 600 essays from 2000 to 2013 has been deeply analyzed in order to unveil those indicators and their trends. Furthermore, strengths and weaknesses are identified, and some remarks that may drive upcoming research are provided. Globally, more than 300 species are reported in the literature, with prevalence of the extraction of seeds (28% of works) and leaves (17%). The main families of extracted compounds, cosolvents and operating conditions adopted are critically examined, being possible to conclude that researchers investigate many times working regions far from the optimum due to practical limitations or absence of experimental optimization. Current phenomenological, statistical and semi-empirical approaches are reviewed, along with scale-up studies, and economic analysis. In the whole, the most comprehensive picture over SFE of vegetable matrices is provided in this review, highlighting pertinent aspects and opportunities that may further consolidate the convincing route of this technology for the next years. (C) 2014 Elsevier B.V. All rights reserved.